Azure Data and AI architect handbook : adopt a structured approach to designing data and AI solutions at scale on Microsoft Azure /: adopt a structured approach to designing data and AI solutions at scale on Microsoft Azure. (2023) - Mertens, Olivier; Baelen, Breght van
No abstract available